Improving Aloud Reading Skills Using Comic Media Assisted Cooperative Script Learning Model in Elementary Schools - Tara Delvina; Rusdial Marta; Yenni Fitra Surya (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to improve reading aloud skills using the cooperative script learning model assisted by comic media in elementary schools. The method used is a class action research method with cycle I and cycle II. The research subjects were class III students at SDN 001 Simalinyang, which consisted of 20 students. Research begins with planning, action, observation, and reflection . Data collection techniques were carried out by tests, observations and documentation. The test is given based on indicators of accuracy of pronunciation (punctuation) in reading, accuracy of pronunciation in reading writing, accuracy of intonation in reading writing, fluency in reading writing, and loudness of voice. The results of the analysis showed that the increase in pre-cycle reading aloud skills was 8 students (40%). After being given action in cycle I there was an increase in the number of students' completeness to 12 students (60%). After being given action in cycle II, there was another increase in the number of completeness to 20 students (100%). In conclusion, the use of the cooperative script learning model assisted by comic media can improve students' reading skills in elementary schools. Keywords : Reading Aloud, Cooperative Script Learning Model, and Comic Media